1995
DOI: 10.4315/0362-028x-58.1.7
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Rapid Technique for Isolation of Escherichia coli O157:H7 from Foods

Abstract: A newly revised enrichment and agar-plating system was tested for selectivity and sensitivity in recovery of unstressed and cold-stressed Escherichia coli O157:H7 from foods. Various foods inoculated with known levels of enterohemorrhagic E. coli O157:H7 (EHEC) were tested by enrichment for 6 h at 37°C in modified tryptic soy broth (mTSB) base supplemented with vancomycin, cefsulodin and cefixime, referred to as EHEC enrichment broth (EEB). Subsequently, portions were spread-plated on sorbitol–MacConkey agar s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
6

Year Published

1996
1996
2008
2008

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 0 publications
1
28
0
6
Order By: Relevance
“…Baylis poor recovery of E. coli O157 using this medium and it was suggested that the concentrations of cefixime and cefsulodin used in VCC may be acting synergistically against strains of E. coli O157. Cefixime at the concentration used in BPW-VCC (0AE05 mg l )1 ) was found by Weagant et al (1995) to inhibit a pure culture strain of E. coli O157:H7 in BPW-VCC but this did not occur in mTSB supplemented with the same antibiotics. For the isolation of VTEC O26 and O111 strains, including the recovery of stressed cells from a variety of foods, Drysdale et al (2004) found that incubation at 42°C in BPW alone and BPW supplemented with 8 mg l )1 vancomycin gave …”
Section: Discussionmentioning
confidence: 97%
“…Baylis poor recovery of E. coli O157 using this medium and it was suggested that the concentrations of cefixime and cefsulodin used in VCC may be acting synergistically against strains of E. coli O157. Cefixime at the concentration used in BPW-VCC (0AE05 mg l )1 ) was found by Weagant et al (1995) to inhibit a pure culture strain of E. coli O157:H7 in BPW-VCC but this did not occur in mTSB supplemented with the same antibiotics. For the isolation of VTEC O26 and O111 strains, including the recovery of stressed cells from a variety of foods, Drysdale et al (2004) found that incubation at 42°C in BPW alone and BPW supplemented with 8 mg l )1 vancomycin gave …”
Section: Discussionmentioning
confidence: 97%
“…Essas linhagens caracterizam-se pela produção de uma toxina chamada de verotoxina (VT) ou "shigalike" toxina (ST), similar à produzida pela bactéria Shigella dysenteriae tipo I [16]. A VT provoca uma doença chamada colite hemorrágica que, em casos mais graves, resulta em um quadro conhecido como síndrome urêmica hemolítica (HUS) [10].…”
Section: -Introduçãounclassified
“…A patogenicidade das cepas EHEC parece estar associada a uma série de fatores, incluindo a produção de várias citotoxinas, coletivamente chamadas de verotoxinas (VTs) ou shiga-like toxinas (SLTs), similares à toxina produzida pela bactéria Shigella dysenteriae tipo I [19,44]. As VTs provocam uma doença chamada de colite hemorrágica que, em casos mais graves, resulta em um quadro conhecido como síndrome urêmica hemolítica (HUS) [30].…”
Section: -Introduçãounclassified
“…A colite hemorrágica tem um período de incubação de 3 a 10 dias e duração de 2 a 9 dias. Os sintomas são diarréia sanguinolenta e dores abdominais severas e, de acordo com a literatura, cerca de 10-15% dos casos agravam-se até o quadro de HUS [18], situação em que ocorre destruição de eritrócitos e falha aguda dos rins, levando à necessidade de diálise, transplante dos rins ou morte [43,44]. A dose infectiva é ainda desconhecida mas, através da compilação de dados de surtos investigados nos Estados Unidos, parece encontrar-se na faixa de 10 células por grama ou mililitro do alimento consumido [18].…”
unclassified